2003
DOI: 10.1128/jb.185.13.3703-3710.2003
|View full text |Cite
|
Sign up to set email alerts
|

mgr, a Novel Global Regulator inStaphylococcus aureus

Abstract: The virulence determinants of Staphylococcus aureus are coordinately controlled by several unlinked chromosomal loci. Here, we report the identification of CYL5614, derived from strain Becker, with a mutation that affects the expression of type 8 capsular polysaccharide (CP8), nuclease, alpha-toxin, coagulase, protease, and protein A. This novel locus, named mgr, was linked by transposon Tn917 and mapped by three-factorial transduction crosses. The region containing the mgr locus was cloned and sequenced. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(162 citation statements)
references
References 34 publications
8
153
1
Order By: Relevance
“…MgrA contains a typical HTH DNA-binding motif and is a member of the MarR family of transcriptional regulators. Similar to CmeR, MgrA also functions as both a repressor and an activator for various genes in Staphylococcus (16,27,43). A recent DNA microarray study indicated that MgrA affects the expression of 355 genes in multiple functional categories in S. aureus (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MgrA contains a typical HTH DNA-binding motif and is a member of the MarR family of transcriptional regulators. Similar to CmeR, MgrA also functions as both a repressor and an activator for various genes in Staphylococcus (16,27,43). A recent DNA microarray study indicated that MgrA affects the expression of 355 genes in multiple functional categories in S. aureus (26).…”
Section: Discussionmentioning
confidence: 99%
“…In Staphylococcus aureus, the MgrA protein serves a pleiotropic global regulator that modulates the expression of multidrug efflux pumps, type 8 capsular polysaccharide, and extracellular proteins (27,43,44). MgrA contains a typical HTH DNA-binding motif and is a member of the MarR family of transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the group include Pseudomonas aeruginosa OspR (63) and MgrA and SarZ in Staphylococcus aureus (54,73). All sense peroxides or other oxidants through the initial oxidation of a sensing cysteine residue (15,16,63).…”
Section: Ohrrmentioning
confidence: 99%
“…The expression of many of these virulence genes is coordinately controlled by regulatory loci, such as two-component regulatory systems (agr, saeRS, srrAB and arlSR) and global transcriptional regulators (sarA, sigB, sarA paralogues, tcaRA, etc.) (Arvidson & Tegmark, 2001;Cheung et al, 1992;Cheung & Zhang, 2002;Luong et al, 2003;, 2006aManna et al, 2004;McNamara et al, 2000;McNamara & Bayer, 2005;Novick, 2003;Projan & Novick, 1997;Truong-Bolduc et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SarA is the first characterized member of the SarA family; others characterized are SarR , SarS (also called SarH1) Tegmark et al, 2000), SarT , Rot (McNamara et al, 2000), SarU (Manna & Cheung, 2003), SarV (Manna et al, 2004), MgrA (Luong et al, 2003;Truong-Bolduc et al, 2003) and SarX (Manna & Cheung, 2006b). The SarA family represents a group of DNA-binding proteins that share homology with each other (20-45 % identity and 45-65 % similarity to SarA protein) as well as with the MarR family of proteins involved in regulating multi-drug resistance in Gram-negative bacteria (Cheung & Zhang, 2002).…”
Section: Introductionmentioning
confidence: 99%